فن السيرة الذاتية بين أبي حامد الزالي ومصطفى محمود: دراسة وظيفية - القاوقجي، عبدالله محمد أديب محمد شمس الدين (جامعة الأزهر - کلیة اللغة العربیة بالمنوفیة, 2022)
يعد الجانب الوظيفي هو الأظهر عند دراسة السيرة الذاتية؛ إذ يقدم هذا الفن خبرات متراكمة تتيح للمتلقين الانتفاع بها في طريق حياتهم، وتأتي سيرة الإمام "الغزالي" مثالا على النموذج المعرفي الإسلامي الذي يقوم على البحث والاستقصاء وصولا إلى الاهتداء للصراط المستقيم، ونلمح وجوه التشابه في هذه التجربة عند الدكتور "مصطفى محمود" من حيث التقلب بين شتى المذاهب والمعتقدات ومجاهدة النفس، كما تتشابه السيرتان من حيث الأسلوب الفني وتقرير الوظيفة، والصيغة التعبيرية، والافتتاح الحكائي، واللغة، والدافع، والبوح، واستبطان النفس، وطريق الوصول. وقد أثمرت الدراسة عن وجود مجموعة من الوظائف تكمن في هذا الفن منها: وظيفة التطهير، ووظيفة استبطان النفس ومحاورتها، ووظيفة النقد للمذاهب الخاطئة وتوجيهها، ووظيفة حب الاستطلاع، ووظيفة التواصل الفكري، ووظيفة المراقبة الاجتماعية، ووظيفة الإمتاع والمؤانسة، ووظيفة القص، كما أفادت هذه الدراسة في بيان أن الأدب أكثر فلسفة من التاريخ، وأن السيرة الذاتية العربية هي موطن العبرة والإفادة دون اللجوء إلى الإسفاف الجنسي أو الأخلاقي، وأن الشخصية الإسلامية ذات روح إيجابية تبث الأمل والتفاؤل في شتى جوانب الحياة، وأن الكاتبين قد اتخذا اللغة الأدبية زيا لسيرتهما، مع أن الموضوع الذي عنيا به موضوع جدلي فلسفي إلا أنهما ببراعة حسهما الأدبي استطاعا أن يخففا من الحمولة الفكرية للموضوع، وأن يجعلانا نواصل القراءة دون إرهاق عقلي أو ملل نفسي، بل ونتشارك معهما في الانفعال العاطفي والتجربة النفسية والمتعة الأدبية، وذلك عبر سلاسة السرد الحكائي، وحسن العرض للأحداث، والألفاظ الموجزة المكتنزة، والعبارات المتزاوجة، والأسلوب القائم على الازدواج والسجعة الرشيقة غير المتكلفة، كما جاءت سيرة الكاتبين نوعا من الرغبة في اتخاذ موقف ذاتي من الحياة، فقد وصلا إلى مذهب خاص بهما ارتاحت له نفسهما بعد دراسة وبحث واستقصاء أمنا معه من الانحراف أو الزيغ، وقد جاءت سيرتهما وثيقة فكرية تدل على ما اكتنز عقلهما من أنواع العلوم والمعارف، وفي الوقت ذاته تثبت ما بذلا من جهد في سبيل الوصول إلى ما اطمأنا له. The functional aspect is most evident when studying the CV; This art presents accumulated experiences that allow recipients to benefit from them in their way of life. The biography of Imam “Al- Ghazali” is an example of the Islamic cognitive model that is based on research and investigation, leading to the guidance of the straight path. We see similarities in this experience with Dr. Mustafa Mahmoud in terms of The fluctuation between the various sects and beliefs and self-fighting, as the two biographies are similar in terms of artistic style, job determination, expressive formula, narrative opening, motivation, revelation, self introspection, language, and the way to reach. The study resulted in the presence of a number of functions that lie in this art, including: the function of purification, the function of inner self-introspection and its dialogue, the function of criticism and guidance of wrong doctrines, the function of curiosity, the function of intellectual communication, the function of social control, the function of enjoyment and sociability, and the function of storytelling. The study shows that literature is more philosophy than history, and that the Arab biography is the home of the lesson and benefit without resorting to sexual or moral abuse, and that the Islamic personality has a positive spirit that inspires hope and optimism in various aspects of life, And that the two writers have adopted the literary language as an outfit for their biography, although the subject they were concerned with is a philosophical polemic, yet by the brilliance of their literary sense they were able to lighten the intellectual load of the subject, and make us continue reading without mental fatigue or psychological boredom, and even share with them the emotional emotion and psychological experience And literary enjoyment, through the smooth narration of the story, the good presentation of events, the concise, chunky words, paired phrases, the style based on duplication and graceful unpretentiousness, The biography of the two writers also came as a kind of desire to take a personal position on life. At the same time, it proves what effort they have made in order to reach what they are assured of.
Keywords: النيسابوري، محمد الغزالي الطوسي، ت. 1111 م. -- محمود، مصطفى، ت. 2009 م. -- السير الذاتية